2021
DOI: 10.1155/2021/4437146
|View full text |Cite
|
Sign up to set email alerts
|

Extraction and Recognition Method of Basketball Players’ Dynamic Human Actions Based on Deep Learning

Abstract: The extraction and recognition of human actions has always been a research hotspot in the field of state recognition. It has a wide range of application prospects in many fields. In sports, it can reduce the occurrence of accidental injuries and improve the training level of basketball players. How to extract effective features from the dynamic body movements of basketball players is of great significance. In order to improve the fairness of the basketball game, realize the accurate recognition of the athletes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…And experiments have shown that this method can increase the accuracy of TOP-1 by 0.6% In order to solve the problem of gradient disappearance caused by the deepening of the network layer, the network designed two branches and added two softmax classifiers at the end of the branches to assist in adjusting the network parameters. Some researchers have proposed to add attenuation coefficients to the two classifiers, but in the end, it is proved through experiments that the improvement is not very meaningful [ 29 , 30 ]. When we actually test, these two extra softmax will be removed, only based on the output result of the main softmax.…”
Section: Convolutional Neural Networkmentioning
confidence: 99%
“…And experiments have shown that this method can increase the accuracy of TOP-1 by 0.6% In order to solve the problem of gradient disappearance caused by the deepening of the network layer, the network designed two branches and added two softmax classifiers at the end of the branches to assist in adjusting the network parameters. Some researchers have proposed to add attenuation coefficients to the two classifiers, but in the end, it is proved through experiments that the improvement is not very meaningful [ 29 , 30 ]. When we actually test, these two extra softmax will be removed, only based on the output result of the main softmax.…”
Section: Convolutional Neural Networkmentioning
confidence: 99%
“…Wang et al used the optical flow feature of a video sequence to realize template matching, but the optical flow is easily affected by noise, so the effect of this method is limited [12]. Liu et al used the word bag model to realize the task of recognizing human behavior, and both achieved the expected recognition results.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Softmax function Computational Intelligence and Neuroscience maps the output of each dimension to the probability value between [0, 1], ensures that the sum of the output of all dimensions is 1, and then calculates its CE loss. Combine equations ( 9) and ( 11) to obtain the Softmax loss function, as shown in equation (12).…”
Section: Activation Functionmentioning
confidence: 99%
“…A quantitative comparison is made between the suggested method and cutting-edge techniques to verify its validity. The experimental outcomes are depicted in figure 3; the contrasted approaches include LRCN [34], ALSTM [35], VideoLSTM [36], and CHAM [37]. When compared to previous approaches, the ARBIGNet suggested in this study can reach 90.5% mAP and 96.5% accuracy, which may be enhanced to varied degrees, demonstrating its superiority.…”
Section: Results and Findingsmentioning
confidence: 85%